The influence of training volume on training and match injury risk in elite Scottish rugby union players - Paul, C.; Campbell, T.; Yule, S.; Walsh, J.; Martindale, R.; Palmer, D. (British Journal of Sports Medicine, 2021)
Background Training volume has been shown to influence injury risk in elite Rugby Union players.